Sosialisasi Pencegahan Stunting Di Wilayah Pesisir Lombok Bagian Barat: Kasus Stunting Di Desa Senggigi, Lombok Barat - Isnaeni, Wilya; Herawati, Tuti; Agustawijaya, Didi S.; Hoesain, Ismail; Sulistyowati, Tri; Muhajirah, Muhajirah (Jurnal Gema Ngabdi, 2024)
The NTB Golden Generation Program (GEN NTB) is a strategy to improve the quality of human resources in West Nusa Tenggara Province since 2012. The target to be achieved from this program is the formation of a healthy, intelligent, devout and productive generation by 2045. In line with the GEN NTB program. Research has been conducted on GEN NTB children aged 4-6, to determine the relationship between OXTR gene mRNA expression and prosocial behavior in GEN NTB children. However, this research focused on the target areas of Central Lombok and East Lombok Regencies. Meanwhile, stunting cases also occur in other districts in NTB Province. To find out the condition of stunting in West Lombok Regency, especially in coastal areas, case identification and socialization are carried out. For this reason, through this community service, motorbikes will be carried out by socializing the causes of stunting, especially the target community is coastal areas. Specifically, the people of Senggigi Village are people who have been marginalized in terms of domicile and employment opportunities due to tourism development in the area. Thus, it is important to make efforts to reduce stunting rates in coastal areas, through socializing the stunting problem in Senggigi Village.